'I hate sand … it gets everywhere'—Phanerozoic sedimentary recycling from NW Africa. (10th October 2022) - Lovell‐Kennedy, James; Roquette, Emmanuel; Schröder, Stefan; Redfern, Jonathan
Abstract: Over 10, 000 published detrital zircon ages have been reprocessed (applying a +10% normal and reverse concordance range) and analysed to understand the evolution of the detrital zircon record of north‐west Africa during the Phanerozoic. Using dissimilarity and clustering analysis, shifts in detrital zircon populations allow interpretation of the evolution of source regions and source to sink systems throughout the Phanerozoic within the West Gondwana superfan. Previous thermochronology and field studies conducted across north‐west Africa indicate significant and sustained shifts in source regions in Meso‐Cenozoic times which are not recorded in the detrital zircon geochronology record. This discrepancy is most notable for Mesozoic to modern source to sink studies focused on the evolution of the Atlasic rift and opening of the Atlantic and Tethyan Oceans to the west and north respectively. Our results indicate a high degree of similarity between samples from Cambrian times onwards due to successive phases of sediment recycling. This highlights the need to integrate detrital zircon analysis with other techniques to provide confident reconstruction of sediment routing systems across Morocco. This systematic review also reveals the ubiquitous occurrence of Mesoproterozoic zircons within Moroccan sediment. No basement of this age is known from north‐west Africa—often described as the 'Mesoproterozoic Gap', which was thought to be a diagnostic feature of sediment derived from the West African Craton. However, zircons of this age form 7% of all analysed zircons and are present in sediments from at least 700 Ma. The presence of this population is interpreted as strongly diagnostic of provenance from either the Amazonian Craton or the Eastern Gondwana Orogen within Central Africa. Their presence in the Moroccan detrital record from the Neoproterozoic onwards raises questions about the position of the West African Craton in the Proterozoic, and for the spatial extent of Mesoproterozoic orogeny within north Africa. Abstract : Key episodes of zircon formation and sedimentary recycling along the North Gondwana margin since Neoproterozoic times.